Influence of Low Dietary Inclusion of the Microalga Nannochloropsis gaditana (Lubián 1982) on Performance, Fish Morphology, and Muscle Growth in Juvenile Gilthead Seabream (Sparus aurata) - María Dolores Ayala; Carolina Galián; Victoria Fernández; Elena Chaves-Pozo; Daniel García de la Serrana; María Isabel Sáez; Alba Galafaz Díaz; Francisco Javier Alarcón; Tomás Francisco Martínez; Marta Arizcun (Animals, 2020)
A 90-d feeding trial was conducted in which five groups of gilthead seabream (11.96 g initial body weight) were fed with a microalgae-free diet (control group, C) or four diets containing the microalgae Nannochloropsis gaditana at two inclusion levels (2.5% or 5%), either raw (R2.5 and R5 batches) or cellulose-hydrolyzed (H2.5 and H5 batches), to study their effect on the body and muscle growth. At 40 days, the highest values of body length and weight were reached in R5 group, but at 64 and 90 days, these were reached in R2.5. However, feed conversion rate, specific growth, daily intake, and survival (100%) were similar in all the groups. The acquisition of a discoid body shape was accelerated depending on the inclusion level of N. gaditana in the diets. Moreover, H5 diet affected the fish geometric morphology compared to R5 diet. The white muscle transverse area was similar in all groups at 40 days, with the exception of H2.5 group, which showed the lowest area. At day 90, C and R2.5 displayed the highest muscle growth, attributable to increased hyperplasia in C, and higher hypertrophy in R2.5. However, the highest proportion of small and medium fibers was observed in R5 and H5.